STUDY ON THE PRODUCTION PROCESS OF SINGLE DOSE MEASLES-RUBELLA COMBINED VACCINE AT POLYVAC (Vietnam Journal of Community Medicine, 2021)
Center for Research and Production of Vaccines and Biologicals (POLYVAC) has conducted “Study on the production process of single dose measles-rubella combined vaccine (MRVAC)” (1dose/vial) in lyophilized form to make it convenient to use for vaccination services and export. The results have determined  the formulation of MRVAC final bulk, freeze-dried process. The quality of researched products met WHO and Vietnam Pharmacopoeia V standards in both visual tests of lyophilized vaccine cake and after being reconstituted with sterile water for injection, the titer of measles virus ranges from 4.03 to 4.28 lgPFU/0.5mL and titer of rubella virus is from 3.79 to 3.98 lgPFU/0.5 mL. Results on thermal stability test when incubating the vaccine at 37oC/7days, the titer of measles virus decreased from 0.79 to 0.96 lgPFU/ 0.5mL and titer of rubella virus decreased from 0 to 0.18 lgPFU/0.5mL. Residual moisture content ranges from 0.35 to 0.72%. pH of vaccine is stable, ranges from 7.42 to 7.62.
Keywords: Measles – Rubella combined vaccine, MRVAC, freeze-dried